Hadith #2788 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abdullah bin Yazid bin Zayd; Ayyash bin 'Abbas al-Qanabi عياش بن عباس القتباني; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Isa bin Hilal عيسى بن هلال; Sa'id bin Abi Ayoub سعيد بن أبي أيوب الخزاعي (Sunan Abi Dawud)
We were staying with the Messenger of Allah (ﷺ) at Arafat; he said: O people, every family must offer a sacrifice and an atirah. Do you know what the atirah is? It is what you call the Rajab sacrifice. Abu Dawud said: ‘Atirah has been abrogated, and this tradition is an abrogated one.
Grade: Hasan